Optimization of biotechnological processes. The acetic acid fermentation. Part I: The proposed model - Jiménez-Hornero, Jorge E.; Santos-Dueñas, Inés M.; García-García, Isidoro (Biochemical engineering journal, 2009)
Vinegar is a food product of increasing significance by virtue of its widely variable origin and uses (particularly as a condiment or food preservative). The gastronomic value of vinegar has been appreciated for thousands of years. The growing social and economic significance of these products has fostered research into the most salient aspects of their production processes. The widespread use of submerged cultures in such processes has aroused an obvious interest in their modelling with a view to facilitating their design, control and optimization. Also, the availability of increasingly powerful utility and dedicated software tools has enabled a much rigorous approach to devising and application of more complex and accurate models for these purposes. This paper (Part I) reviews previous attempts at modelling acetic acid fermentation and proposes a new mathematical model for the process based on extensive experimental testing. The model introduces new equations and considers cell lysis during the process. Part II is devoted to study the key subject of parameter estimation and finally Part III deals with the optimization task. Though the wine vinegar process is being considered, many of the studied issues could be applied to other fermentations.